Maintenance Management Performance – An Overview towards Evaluating Malaysian Palm Oil Mill - Baluch, Nazim; Abdullah, Che Sobry Bin; Mohtar, Shahimi Bin (The Asian Journal of Technology Management (AJTM), 2010)
Deficient maintenance management can severely affect competitiveness of an organization byreducing throughput, increasing inventory, and leading to poor performance. Performancecannot be managed without measurement: it provides the required information to themanagement for effective decision making; and is used by industries to assess progressagainst set goals and objectives in a quantifiable way for effectiveness and efficiency. For thepalm oil mills to stay competitive, it is imperative that they elevate the maintenancemanagement role; from a cost center to the strategic partner in business. This paperhighlights how measuring maintenance performance helps us identify the factors causing poorperformance, and provides an opportunity to improve company’s profits.Key words: key performance indicators, lean, total productive maintenance